IMPROVING AN EXISTING OR ERECTING A NEW OR ADDITIONAL STRUCTURE BY ESTA OCCUPIERS: AN ANALYSIS OF Daniels v Scribante 2017 (4) SA 341 (CC), Erasmus v Mtenje [2018] ZALCC 12, and De Jager v Mazibuko [2020] ZALCC 7 - Lerato Rudolph Ngwenyama (Obiter, 2024)
The conduct of occupiers (i.e., occupiers in terms of the Extension of Security of Tenure Act 62 of 1997 (ESTA)) was central in three court judgments in recent years. The first judgment in the matter of Daniels v Scribante (2017 (4) SA 341 (CC)) is widely regarded as a progressive and transformative judgment, and as having opened the door for ESTA occupiers to improve their dwellings. In Daniels v Scribante, the Constitutional Court considered whether an ESTA occupier has a right to make improvements to a dwelling to make it habitable. The court found that ESTA affords an occupier the right to make improvements to their dwelling without the consent of the owner. However, the court pointed out that meaningful engagement between an owner or person in charge and an ESTA occupier was still necessary, because the exercise of an occupier’s right to make improvements could potentially encroach on an owner’s right to property. Since the judgment in Daniels was delivered, some ESTA occupiers, without prior consent or engaging meaningfully with the owner or person in charge, have improved or erected new structures – both inside and outside the demarcated parcel of land where they reside. Despite the ESTA occupiers’ need to improve or erect new structures, Daniels is context-sensitive and is therefore not blanket authority to engage in building operations anywhere on private farmland without prior, meaningful engagement with the owner or person in charge. Furthermore, reliance on Daniels v Scribante must be clearly justified. It is in this context that the case note emphasises that, where the current dwellings of ESTA occupiers are not suitable for human habitation and it is necessary to improve them or erect new buildings, the improvement must be done after proper meaningful engagement between the ESTA occupier and the owner or person in charge in accordance with the general guidelines set out in Daniels v Scribante. This is because the principles established in Daniels v Scribante set the scene for the much-needed balancing of rights between ESTA occupiers and owners, by alluding to the fact that ESTA occupiers are obliged to engage meaningfully with owners or persons in charge prior to embarking on improving or building new structures. The first part of this case note sets out and analyses case law that has dealt with improving or building new structures. The next part explores the competing rights and interests of ESTA occupiers and owners in relation to improving or erecting new structures. The third and final part of the contribution highlights and emphasises the importance of meaningful engagement before an ESTA occupier improves or erects a new dwelling on property belonging to another.